Green eggs and ham - Seuss, Dr. (New York : Beginner Books, 1988)
Sam-I-am relentlessly pursues a furry top-hatted creature trying every way he can think of to get the creature to eat green eggs and ham. The well-known, cleverly illustrated creatures and the silly rhyming text are perpetual favorites of young children.
Reprint. Originally published: New York : Beginner Books, 1960.
"B-16"--Spine.
Decoding demand: 6 (very low) Semantic demand: 10 (very low) Syntactic demand: 17 (very low) Structure demand: 28 (low)
210L
Accelerated Reader
Accelerated Reader AR
Keywords: Eggs -- Juvenile fiction; Ham -- Juvenile fiction; Stories in rhyme -- Juvenile literature